QT interval dynamics in patients with ST-elevation MI - Mann, Tomer; Moses, Amit; Yesaulov, Anastasiea; Hochstadt, Aviram; Granot, Yoav; Rosso, Raphael; Shacham, Yacov; Chorin, Ehud (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background: Background: An association between excessively prolonged QTc and ventricular arrhythmia in patients with ST-elevation myocardial infarction has been described; however, the QTc dynamics, characterization, and long-term predictive value are not well known. Objective: To characterize QT interval dynamics in patients undergoing STEMI and determine its association with mortality. Methods: A retrospective analysis of 4,936 consecutive patients, hospitalized for STEMI between 01/2013-12/2021. Patients with less than three ECGs during index hospitalization were excluded. Baseline demographics, cardiovascular history, clinical risk factors, treatment measures, laboratory results, and mortality data were retrieved from the hospital’s electronic medical records. Results: We included 1054 patients and 5021 ECGs in our cohort with a median follow-up of 6 years (IQR 4.3-7.4 years). The QTc was longer in women in comparison to men (428.6 ms +/- 33.4, versus 419.8 ms +/-32.52, P value=0.001). QTc prolongation was greater in females, elderly patients, and patients with STEMI caused by occlusion of the left anterior descending (LAD) coronary artery. We determined QTc cutoff to be 445 ms. This value of QTc divided our cohort upon arrival into a long QT group (217 patients, 26% of the cohort) and a “normal” QT group (835 patients, 74% of the cohort). The long QT group experienced an increase in combined short and long terms all-cause mortality. The QTc upon arrival, on day 2 of hospitalization, and before discharge from the hospital, correlated with long-term mortality. Conclusion: QTc duration is often prolonged during STEMI; this prolongation is associated with increased mortality and adverse events. Gender is an important mediator of QTc dynamics. Keywords: QTc, STEMI, Dynamics, All-cause Mortality, Gender.